Application of low-temperature plasma technology in the field of agriculture - Zhang, Bo (Transactions on Environment, Energy and Earth Sciences, 2024)
The low-temperature plasma crop seed treatment technology has opened up a new way for the application of plasma in crops, creating a new path for high and stable yield of crops, and enriching agricultural yield increasing technology. This article briefly describes the innovative development of low-temperature plasma seed treatment technology, introduces the series of applications of plasma technology in crop seeds, as well as the biological effects and activation mechanisms of plasma. It also looks forward to the development and application prospects of plasma seed treatment technology.